Non-operative treatment for lumbar spinal stenosis with neurogenic claudication: an updated systematic review. Issue 1 (19th January 2022) - Ammendolia, Carlo; Hofkirchner, Corey; Plener, Joshua; Bussières, André; Schneider, Michael J; Young, James J; Furlan, Andrea D; Stuber, Kent; Ahmed, Aksa; Cancelliere, Carol; Adeboyejo, Aleisha; Ornelas, Joseph
Abstract : Objectives: Neurogenic claudication due to lumbar spinal stenosis (LSS) is a growing health problem in older adults. We updated our previous Cochrane review (2013) to determine the effectiveness of non-operative treatment of LSS with neurogenic claudication. Design: A systematic review. Data sources: CENTRAL, MEDLINE, EMBASE, CINAHL and Index to Chiropractic Literature databases were searched and updated up to 22 July 2020. Eligibility criteria: We only included randomised controlled trials published in English where at least one arm provided data on non-operative treatment and included participants diagnosed with neurogenic claudication with imaging confirmed LSS. Data extraction and synthesis: Two independent reviewers extracted data and assessed risk of bias using the Cochrane Risk of Bias Tool 1. Grading of Recommendations Assessment, Development and Evaluation was used for evidence synthesis. Results: Of 15 200 citations screened, 156 were assessed and 23 new trials were identified. There is moderate-quality evidence from three trials that: Manual therapy and exercise provides superior and clinically important short-term improvement in symptoms and function compared with medical care or community-based group exercise; manual therapy, education and exercise delivered using a cognitive-behavioural approach demonstrates superior and clinically important improvements in walking distance in the immediate to long term compared with self-directed home exercises and glucocorticoid plus lidocaine injection is more effective than lidocaine alone in improving statistical, but not clinically important improvements in pain and function in the short term. The remaining 20 new trials demonstrated low-quality or very low-quality evidence for all comparisons and outcomes, like the findings of our original review. Conclusions: There is moderate-quality evidence that a multimodal approach which includes manual therapy and exercise, with or without education, is an effective treatment and that epidural steroids are not effective for the management of LSS with neurogenic claudication. All other non-operative interventions provided insufficient quality evidence to make conclusions on their effectiveness. PROSPERO registration number: CRD42020191860.